Marketing Research on Food Consumers' Behavior in Georgia's Consumer Market - N. Maghlakelidze K., Todua (British Journal of Marketing Studies, 2019)
The marketing survey of thirty products has been included in the consumer basket of Georgia. Information obtained from the respondents' surveys on the current and consumable acceptable prices of products are used by this information to construct linear, indicative and linear models to reflect the change in time.